Somatic mutation analysis of Mesonephric-Like adenocarcinoma and associated putative precursor Lesions: Insight into pathogenesis and potential molecular treatment targets - Elizabeth Arslanian; Kamaljeet Singh; C. James Sung; M. Ruhul Quddus (Elsevier, 2022)
Aims: Mesonephric-like adenocarcinoma (MLA) is a recently described histologic tumor subtype of the Müllerian tract. MLA can arise in association with Müllerian lesions that share common mutations. We report three MLAs and hypothesize that concurrent endometriosis and cystadenofibroma with focal borderline changes might also carry common mutations. Methods and results: We searched "mesonephric" in our database from 2015 to mid-2021 to retrieve MLA cases. Somatic mutation analysis was performed on tumors and on associated benign proliferative lesions. All MLAs (2 ovarian and 1 uterine) harbored KRAS G12D or G12 V mutations. A PIK3CA alteration (H1047Q) was detected in one MLA and in the associated cystadenofibroma with focal borderline changes. The molecular profile of MLA-associated Müllerian lesions (endometriosis and seromucinous cystadenofibroma with focal borderline changes) was similar to concurrent adenocarcinoma. However, tumor contamination could not be excluded in the endometriotic lesion. Patients presented at various stages, with no evidence of post-operative recurrence after 15 months (FIGO IC) and 33 months (FIGO IIA2). One patient (FIGO IIIA1) died of disease 32 months after surgery. Conclusions: KRAS mutations commonly characterize MLA. At least some MLA-associated Müllerian lesions show MLA-like genetic profiles, suggesting a precursor role. As far as we are aware, we describe for the first time in MLA the potentially actionable H1047Q variant of PIK3CA.